A severed head - Murdoch, Iris, ....- (Harmondsworth : Penguin, 1976)
Martin Lynch-Gibson believes he can possess both a beautiful wife and a delightful lover. But when his wife, Antonia, suddenly leaves him for her psychoanalyst, Martin is plunged into an intensive emotional reeducation. He attempts to behave beautifully and sensibly. Then he meets a woman whose demonic splendor at first repels him and later arouses a consuming and monstrous passion. As his Medusa informs him, “this is nothing to do with happiness.”
Keywords: Fiction